Occurrence of Toxigenic Microcystis spp in Major Water Bodies of North East India - Rajkonwar, Jadab; Bora, Ajitabh; Reddy, Pichili Vijaya Bhaskar; Dwivedi, Sanjai Kumar (Defence Life Science Journal, 2020)
Toxigenic cyanobacterial blooms in the water bodies represent a major ecological problem around the world. Some species produces a diverse range of toxins that have hepatotoxic, neurotoxic, cytotoxic and dermatoxic activity and hence have deleterious effect on humans, animals and fishes leading to death as well. Cultural eutrophication of water bodies leads to increased incidence of these harmful cyanobacterial blooms worldwide. North-East India being a biodiversity hotspot harbor many species of cyanobacteria. Few reports suggested presence of few toxigenic cyanobacteria in the water bodies of Assam, but no systematic studies have been undertaken to evaluate their toxicity. This work is being conducted to gather information on major toxigenic cyanobacteria, with special emphasis to microcystin (a cyclic heptapeptides with high acute and chronic toxicities to humans and animals) producing strains. Water samples have been collected from few water bodies of North-East and enriched in specific media. The toxin Microcystin was detected using specific ELISA kit and positive results have been obtained. Further, 16s rDNA sequencing was employed for molecular identification of the strains.